T-T-T diagram of serpentine and saponite, and estimation ofmetamorphic heating degree of Antarctic carbonaceous chondrites - Akai, Junji (National Institute of Polar Research, 1992)
P(論文) For the estimation of peak thermal metamorphic degree of phyllosilicates in Antarctic carbonaceous chondrites, heating experiments of serpentine and saponite were carried out. A T-T-T diagram of serpentine for elevated temperature was obtained by heating the serpentine in the Murchison CM2 chondrite in vacuo at different temperatures (250∿1100℃) and for different durations (1 hour to 350 hours). Serpentine decomposed into olivine and enstatite through characteristic transitional structures. First decomposition started at about ∿300℃, the transitional structure appears at ca. 400∿500℃, and well-crystallized olivine and enstatite appeared above ∿750℃. In the T-T-T diagram, a minor time dependence was found. A T-T-T diagram of saponite was obtained in a similar was using terrestrial Fe-saponite. Saponite maintained its structure till about 800∿900℃, then decomposition started and finally enstatite was formed. New data on thermally affected phyllosilicates in Yamato (Y)-793321 indicate coexistence of 7Å unaltered serpentine and a transitional structure. Thermally affected saponite in Belgica (B)-7904 was also documented. Based on the T-T-T diagrams, the peak metamorphic degrees and peak temperatures were estimated in the order of B-7904≥Y-86720>Y-82162>Y-793321. departmental bulletin paper